Growth and productivity of traditional scented rice in organic cultivation - ., Supriya; Singh, DK; Yaying, Monica; Verma, Parkash; Kumar, Birendra; Garg, Kamal (ORYZA-An International Journal of Rice, 2023)
Utilizing the production potential of scented rice verieties via organic farming methods is a viable option to support the increasing population’s food needs. Employing organic nutrient sources like Sesbania and vermicompost has the potential to significantly enhance rice yield and positively impact soil quality, presenting a promising approach. In order to study the effect of organic mode of cultivation on ten different scented rice varieties namely Kubri Mamhani, Kudrat-5, Chinar-20, Kesho Pohu, DRK, Kudrat-5, Pusa-1121, Type-3, Taraori and Tilak Chandan in tarai region of Uttarakhand, India, a field experiment was conducted at the Norman E. Borlaug Crop Research Centre, located within G. B. Pant University of Agriculture and Technology in Pantnagar, Uttarakhand, during the kharif season of 2020. The varieties were evaluated in Randomized Block Design with three replications. The results revealed that the application of organic source of nutrients significantly improved the growth parameters and yield of scented rice over control. Among the varieties, Kudrat-5 recorded higher values for tiller/m2 (273) and grain yield (42.46 q/ha). Application of organic matter in the form of Sesbania and vermicompost significantly produced higher plant height, tillers/m2, culm height, culm thickness, days to 50% flowering, straw yield and harvest index. So, it is inferred that ten scented rice varieties differ widely among themselves when grown under organic cultivation. In terms of grain yield Kudrat-5 variety performed better under organic production system.